Large-scale Au nanoparticle cluster arrays with tunable particle numbers evolved from colloidal lithography. (27th July 2018) - Fang, Liping; Liu, Xueyao; Xiang, Siyuan; Liu, Wendong; Shen, Huaizhong; Li, Zibo; Zhang, Kai; Song, Wei; Yang, Bai
Abstract: The assembly of metal nanoparticles (NPs) can regulate their plasmon resonance properties to pursue the best properties for applications. However, the controllable assembly of large-scale metal NP cluster arrays remains a significant challenge. This paper presents a novel strategy to prepare large-scale Au NP cluster arrays based on colloidal lithography and template-guided self-assembly technique. The NPs arrays are fabricated by introducing Au NPs onto the quaternized poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA) brush templates via electrostatic interaction. The number of Au NPs in cluster can be arbitrarily tuned by changing the surface area of the polymer templates created by colloidal lithography, which resulted in tunable plasmonic properties. The prepared Au NP cluster arrays were used for surface enhanced Raman scattering (SERS) and the SERS properties of the Au NP cluster arrays were studied.